2020
DOI: 10.1002/maco.202011507
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ga and Sn on the electrochemical behavior of Mg–6Al–1Zn as anode materials

Abstract: The microstructure and electrochemical behavior of Mg–6Al–1Zn, Mg–6Al–1Zn–1Ga, Mg–6Al–1Zn–1Sn, and Mg–6Al–1Zn–0.5Sn–0.5Ga as anode materials in a 3.5 wt% NaCl solution are compared systematically. The results show that Sn alloying refines the second‐phases of Mg–6Zn–1Al by promoting tiny granular Mg17Al12 phases containing Sn, and inspires their disperse distribution. However, the Ga results in the formation of semicontinuous reticular Ga containing Mg17Al12 phases. The comparison of discharge tests indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…[ 1,2 ] This is due to their high energy density, high capacity, and low cost. [ 2–5 ] Nowadays, most research studies focus on magnesium or magnesium alloys as anodes for seawater‐activated batteries. [ 1–7 ] However, there is relatively less research focusing on aluminum alloys as anodes for seawater batteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1,2 ] This is due to their high energy density, high capacity, and low cost. [ 2–5 ] Nowadays, most research studies focus on magnesium or magnesium alloys as anodes for seawater‐activated batteries. [ 1–7 ] However, there is relatively less research focusing on aluminum alloys as anodes for seawater batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2–5 ] Nowadays, most research studies focus on magnesium or magnesium alloys as anodes for seawater‐activated batteries. [ 1–7 ] However, there is relatively less research focusing on aluminum alloys as anodes for seawater batteries. This is because aluminum anodes face severe passivation behavior in seawater electrolytes, which is due to the inherent oxide film and subsequent product layer formed on its surface.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the above issues and promote the application of aqueous Mg batteries, developing a highperformance Mg alloy is one of the most important approaches. During the past decades, studies of Mg anodes mainly focused on heavily alloyed Mg alloys, that is, Mg-Al-Zn-(Ga, Sn), [5][6][7][8] Mg-Al-In, [9] Mg-Al-Pb-(Ce, Y, La), [10][11][12] Mg-Al-Sn-Mn, [13,14] and Mg-Li-Al-(Zn, Ce, Y) [15][16][17] alloys. Accordingly, it can be found that Al is a widely used alloying element in the Mg alloy anode.…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7] Among these elements, tin is an environment friendly activator and the magnesium anodes with the addition of tin, such as Mg-Al-Sn, Mg-Al-Zn-Sn-Ga, Mg-Sn-Zn-Ag, and Mg-Sn-Mn-Ca, have received increasing attention recently. [8][9][10][11][12][13] Based on the compositional optimization, grain refinement and dispersion of fine second phases further improve the anode performance since these modifications not only alleviate side reaction but also benefit the uniform dissolution of magnesium anode, thus abating the chunk effect in the course of discharge. 1,3,5,14 Plastic deformation such as rolling and extrusion are common approaches to refine the grains of magnesium anodes; [15][16][17] however, the high density of dislocations and strong grain orientation are also created during the deformation processes.…”
mentioning
confidence: 99%